Chicken farm monitoring system - Md. Abas, Abd Muiz Fathi; Amir, Nur Syamimi; Azmi, Nur Anis; Zainal Abidin, Zulkifli; Shafie, Amir Akramin (The Institute of Electrical and Electronics Engineers, Inc., 2016)
In this paper, the chicken farm monitoring system is proposed and developed based on wireless communication unit to transfer data by using the wireless module combined with the sensors that enable to detect temperature, humidity, light and water level values. This system is focused on the collecting, storing, and controlling the information of the chicken farm so that the high quality and quantity of the meal production can be produced. This system is developed to solve several problems in the chicken farm which are many human workers is needed to control the farm, high cost in maintenance, and inaccurate data collected at one point. The proposed methodology really helps in finishing this project within the period given. Based on the research that has been carried out,the system that can monitor and control environment condition (temperature, humidity, and light) has been developed by using the Arduino microcontroller. This system also is able to collect data and operate autonomously.